Screening of host proteins interacting with the African swine fever virus outer membrane protein CD2v - Chen, Xiong-nan; Zhu, Gao-xi; Li, Yi-xian; Hao, Yi-han; Liang, Yi-fan; Hu, Chen; Sun, Ying-shuo; Peng, Yun-zhao; Li, Xi; Huang, Zhao; Zhang, Gui-hong; Gong, Lang; et al. (Frontiers in Microbiology, 2025)
BackgroundThe African swine fever virus (ASFV) is a highly pathogenic double-stranded DNA virus that poses a significant threat to the global swine industry. Although the CD2v protein encoded by ASFV is a key factor in viral immune evasion and pathogenicity, the mechanism underlying its interaction with host proteins remains unclear.MethodsThe aim of this study was to identify a range of potential host proteins that interact with the CD2v protein using the membrane yeast two-hybrid technology.ResultsThrough subsequent validation experiments and functional analyses, we discovered that these proteins are involved in critical cellular processes such as translational regulation, inflammatory responses, immune signaling, and iron metabolism. Furthermore, interaction network and functional enrichment analyses revealed that ASFV might influence host cell functions through multiple pathways to facilitate viral replication.ConclusionThis study provides new insights into the pathogenic mechanisms of ASFV and offers valuable clues for identifying antiviral targets.